2010
DOI: 10.1016/j.jtcvs.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondrial DNA alterations in esophageal squamous cell carcinomas

Abstract: We demonstrated that somatic D310 mutations and increase in the copy number of mitochondrial DNA are of clinical importance in esophageal squamous cell carcinoma. We also propose a model of DNA instability and clonal expansion during the carcinogenesis and progression of esophageal squamous cell carcinoma from the viewpoint of mitochondrial DNA transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 21 publications
(43 reference statements)
6
95
1
1
Order By: Relevance
“…These tissue samples were stored in 1.5-ml Eppendorf vials and mixed with 500 µl xylene (Merck KGaA, Darmstadt, Germany) at room temperature for 16 h. After centrifuging at 10,000 x g for 10 min at room temperature and discarding the supernatants, these tissue samples were re-hydrated with 100, 80, 60 and 40% alcohol aqueous solution and then pure distilled water for 5 min in steps. Finally, the hydrated tissue samples were mixed with 200 µl QuickExtract DNA extraction solution (Epicenter, Madison, WI, uSA) plus 3 µl of 5% butylated hydroxytoluene in methanol to extract total cellular DNA at 65˚C for 3 h as previously described (19,20). The DNA sample was kept at -20˚C until use.…”
Section: Patient Selection Tissue Preparation and Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tissue samples were stored in 1.5-ml Eppendorf vials and mixed with 500 µl xylene (Merck KGaA, Darmstadt, Germany) at room temperature for 16 h. After centrifuging at 10,000 x g for 10 min at room temperature and discarding the supernatants, these tissue samples were re-hydrated with 100, 80, 60 and 40% alcohol aqueous solution and then pure distilled water for 5 min in steps. Finally, the hydrated tissue samples were mixed with 200 µl QuickExtract DNA extraction solution (Epicenter, Madison, WI, uSA) plus 3 µl of 5% butylated hydroxytoluene in methanol to extract total cellular DNA at 65˚C for 3 h as previously described (19,20). The DNA sample was kept at -20˚C until use.…”
Section: Patient Selection Tissue Preparation and Dna Extractionmentioning
confidence: 99%
“…The sequences of primers used for nDNA amplification (18S rRNA region) were: 18SF1546, 5'-T AGAGGGACAAGTGGCGTTC-3'; and 18SR1650, 5'-CGCT GAGCCAGTCAGTGT-3' (21). The equations of standard curves set for mtDNA and nDNA quantification were set as previously described (19,20,22). Then the mtDNA and nDNA copies of the clinical samples relative to mtDNA and nDNA copies of the 143B osteosarcoma cells were calculated.…”
Section: Standard Curves For Mtdna and Ndna Quantificationsmentioning
confidence: 99%
“…Numerous reports have indicated that the copy number of mtDNA changes in various types of cancer (6)(7)(8)(9)(10)(11)17). In 1989, Yamamoto et al first reported the increased mitochondrial genomic expression in pre-malignant lesions of the colon in patients with pre-cancerous familial polyposis coli (18).…”
Section: A B Cmentioning
confidence: 99%
“…The copy number is reduced in hepatocellular and renal cell carcinomas and breast cancer (6)(7)(8). However, it is increased in head and neck and ovarian cancers and esophageal squamous cell carcinomas (9)(10)(11). However, whether and and the manner in which mtDNA copy number changes in colorectal cancer remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…이 결과를 Bionics Inc. (Seoul, Korea)에 의 뢰하여 ABI 3730 DNA sequencer를 이용하여 직접 염기 서열분석을 시행하여 결과를 분석하여 D310과 D514의 다형성을 확인하였다. 미토콘드리아의 복제수는 real-time PCR의 방법으로 β-actin을 이용하여 input DNA의 양을 표준화하여 측정 하였다 [13,17]. 이가 종양에서 높게 나타나는 것을 보고하였다 [19].…”
Section: 재료 및 방법unclassified